2018
DOI: 10.1007/s11244-018-1061-8
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Electrochemical Cells to Study the Oxygen Evolution Reaction by Near Ambient Pressure X-ray Photoelectron Spectroscopy

Abstract: In this contribution, we report the development of in situ electrochemical cells based on proton exchange membranes suitable for studying interfacial structural dynamics of energy materials under operation by near ambient pressure X-ray photoelectron spectroscopy. We will present both the first design of a batch-type two-electrode cell prototype and the improvements attained with a continuous flow three-electrode cell. Examples of both sputtered metal films and carbon-supported metal nanostructures are include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 58 publications
(101 reference statements)
0
33
0
Order By: Relevance
“…Because of this fact, the electrified interfaces are inaccessible directly to the common surface sensitive techniques like photoelectron spectroscopy, requiring new experimental strategies for their operation under these conditions [12]. Recently different approaches were developed enabling the investigation of the electronic structure variation of electrodes under potentiostatic control using near ambient pressure X-ray photoelectron spectroscopy (NAPXPS) [13], from gas phase up to bulk aqueous electrolyte [11,12,[14][15][16][17][18]. Some of the most extensively used approaches entail the use of hard X-rays to allow the photoelectrons to escape through thick electrode membranes [19] (a few nanometers thick) or thin film electrolytes [20].…”
Section: Introductionmentioning
confidence: 99%
“…Because of this fact, the electrified interfaces are inaccessible directly to the common surface sensitive techniques like photoelectron spectroscopy, requiring new experimental strategies for their operation under these conditions [12]. Recently different approaches were developed enabling the investigation of the electronic structure variation of electrodes under potentiostatic control using near ambient pressure X-ray photoelectron spectroscopy (NAPXPS) [13], from gas phase up to bulk aqueous electrolyte [11,12,[14][15][16][17][18]. Some of the most extensively used approaches entail the use of hard X-rays to allow the photoelectrons to escape through thick electrode membranes [19] (a few nanometers thick) or thin film electrolytes [20].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic voltammetry (CV) is an electrochemical method that measures the current in an electrochemical cell while cycling the potential of the working electrode (WE) [ 6 ]. Microfluidic electrochemical cells enable similar CV studies of micro- and nanomaterials [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…[58] In order to decouple the contributors to performance losses, and provide a more realistic picture of the degradation phenomena involved, in situ and in operando studies are paramount as shown for OER model systems. [89][90][91] A recent study from Kang et al used gold ribbon sense wires to measure though-plane voltage losses under cell operation. [92] These confirmed that CCMs, specifically the CL/PTL interfacial contact resistance, have the highest contribution in high-frequency resistance losses: 100-fold than that of anode and cathode current collectors.…”
Section: Catalyst Performance and Degradation In Mea Systemsmentioning
confidence: 99%